Autophagy-induced NR2F1 activation promotes the apoptosis of lens epithelial cells and facilitates cataract-associated fibrosis through targeting STAT3 - Hangjia Zuo; Xianyang Liu; Bingjing Lv; Ning Gao; Miaomiao Du; Xiang Gao; Yongguo Xiang; Rongxi Huang; Meiting Lin; Yakun Wang; Yonglin Chen; Hong Cheng; et al. (Genes and Diseases, 2025)
Cataracts, a widely prevalent ocular pathology, engender visual impairment and emerge as a primary etiological factor contributing to ocular blindness. Substantial evidence substantiates that epithelial–mesenchymal transition stands prominently among the pivotal causative factors associated with this debilitating condition. However, the underlying mechanism remains unclear. In the present study, we analyzed the single-cell data and found that the mRNA expression of nuclear receptor subfamily 2 group F member 1 (NR2F1/COUP-TFI) was notably decreased in fibrocytes compared with epithelium. Interestingly, we observed a significant up-regulation of NR2F1 protein in the anterior subcapsular cataract mice model and transforming growth factor-β1 (TGF-β1)-treated SRA01/04 cells. Furthermore, we found that TGF-β1 stimulation disrupted the balance of autophagy, leading to impaired degradation and increased protein levels of NR2F1 in SRA01/04 cells. Subsequently, after anterior chamber injection of NR2F1 adeno-associated virus in anterior subcapsular cataract mice, the development of fibrosis was alleviated. In vitro, the knockdown of NR2F1 in SRA01/04 also mitigated the TGF-β1-induced epithelial–mesenchymal transition. Mechanically, NR2F1 proteins directly interacted with the promoter region of STAT3 and orchestrated the up-regulation of phosphorylated STAT3 (p-STAT3), thereby facilitating the apoptosis and migration of SRA01/04 cells via the JAK1/STAT3 pathway, resulting in epithelium fibrosis and cataracts. Furthermore, inhibition of p-STAT3 obviously attenuated apoptosis and fibrosis of SRA01/04 cells. Collectively, our study provides a novel therapeutic target for cataracts and offers insight into the underlying mechanism of the epithelial–mesenchymal transition of cataracts.